Microwave-assisted encapsulation of blue pea flower (clitoria ternatea) colourant: maltodextrin concentration, power, and time - Marsin, A. M. (Italian Association of Chemical Engineering - AIDIC, 2020)
Blue pea flower (BPF) is one of the natural anthocyanin colourant sources in the world used in food and cosmetic products. Natural colourants are unstable and thus must be encapsulated. The BPF colourant could retain its colour during storage via microwave-assisted encapsulation. This study evaluated the effect of maltodextrin concentration, microwave power, and encapsulation time on the stability of encapsulated BPF colourant. The colourant was extracted from the BPF via microwave-assisted extraction at 770 W for 1 min. For encapsulation, the concentration of the coating material, maltodextrin, was varied from 20 % to 50 %, a microwave power from (550 to 1100) W, and an encapsulation time from (6 to 8) min. The quality of the encapsulated BPF colourant powder was characterised by total anthocyanin content (TAC), the colour parameter index b* value, and the water activity value. A TAC of 27.03 mg/L, a colour parameter index b* value of -9, a water activity of 0.4941, and an encapsulation efficiency of 73.24 % were obtained when the microwave-assisted encapsulation process was performed using 40 % MD at 770 W for 7 min. With pH adjustment, the blue BPF colourant can be turned into other pigments. The findings of this study can be used as a future reference for developing BPF colourant powder using the microwave-assisted method.